Age-dependent cytokine surge in blood precedes cancer diagnosis - Guangbo Chen; Azam Mohsin; Hong Zheng; Yael Rosenberg-Hasson; Cindy Padilla; Kavita Y. Sarin; Cornelia L. Dekker; Philip Grant; Holden T. Maecker; Ying Lu; David Furman; Shai Shen-Orr; et al. (Proceedings of the National Academy of Sciences, 2025)
Aging is associated with increased variability and dysregulation of the immune system. We performed a system-level analysis of serum cytokines in a longitudinal cohort of 133 healthy individuals over 9 y. We found that cancer incidence is a major contributor to increased cytokine abundance variability. Circulating cytokines increase up to 4 y before a cancer diagnosis in subjects with age over 80 y. We also analyzed cytokine expression in 10 types of early-stage cancers from The Cancer Genome Atlas. We found that a similar set of cytokines is upregulated in tumor tissues, specifically after the age of 80 y. Similarly, cellular senescence activity and CDKN1A/p21 expression increase with age in cancer tissues. Finally, we demonstrated that the cytokine levels in serum can be used to predict cancers among subjects age at 80+ y. Our results suggest that latent senescent cancers contribute to age-related chronic inflammation.